Cyanidin as potential anticancer agent targeting various proliferative pathways. (21st November 2022) - Safdar, Muhammad Azhaf; Aslam, Rana Muhammad Nabeel; Shakeel, Amna; Shiza,; Waqar, Mashael; Jmail, Abdullah; Mehmood, Malik Hassan; Gul, Humaira
Abstract: A natural compound cyanidin, which is a type of anthocyanin present in pigmented leaves, fruits, and flowers; distributed widely in berries, apples, and oranges possess anticancer activities, thus curing various types of cancer such as breast, liver, lung, prostate, and thyroid cancer. The article provides an insight into the potential of using a single phytochemical, cyanidin to treat various cancer types including breast, liver, lung, prostate, and thyroid cancer. Information about cyanidin and its pharmacological impact on cancer was collected from books, scientific journals, and reports through electronic data search (Web of Science, Scifinder, PubMed, Scopus, Google Scholar, Elsevier, Springer, Wiley, ACS, Science Direct, CNKI as well as Kew Plants of the Word Online) and library. Cyanidin produces its effects against cancer probably by inhibiting (RAS, MAPK) and activating (caspases‐3 and P‐38) innovative molecular pathways. It may cause cell cycle arrest, cell differentiation processes and changes in redox status which trigger the cytotoxic chemotherapeutic effects. However, it also optimizes the chemotherapeutic targets which are cancer cells less responsive to chemotherapy. Cancer is considered the most widely spread disease and cyanidin from natural origin provides an essential role in treatment of cancer by approaching various mechanistic pathways. Abstract : Plant derived phenolic compound "Cyanidin" potentially targeting breast, liver, lungs, prostate, and thyroid cancer via several molecular and cellular pathways.